Contaminated Groundwater by Nitrate in Sidoarum Village, Godean District, Sleman Regency, Special Region of Yogyakarta - Herwin Lukito; Ekha Yogafanny; Suharwanto Suharwanto; Sektiana Uyun Azizah; Vindy Fadia Utama; Novia Devi Savitri (Fakultas Teknologi Mineral, Universitas Pembangunan Nasional (UPN), 2021)
Sidoarum Village, Godean District, Sleman Regency, Special Region of Yogyakarta become one of the developing areas for getting influenced by Yogyakarta City center which is only 8 kilometers away. Population growth has occurred from 2010 to 2019 which has led to land use changes from agricultural areas to residential areas. Land use change, population growth, incorrect space using, excessive use of fertilizers, agricultural activities, and industrial waste disposal affects the groundwater quality resources, especially nitrate (NO3) compound. This research was aimed to determine the distribution of groundwater quality based on nitrate parameters and to analyze the relationship between land use changing and nitrate concentrations in groundwater. This mixed-method research used to survey and mapping methods to collect the data. The analysis was conducted by laboratory tests and spatial analysis method using Arc GIS software. The sampling of groundwater was carried out by purposive sampling method based on differences in land use. The results indicated that most of the groundwater in Sidoarum Village has been contaminated by nitrate due to activity in agricultural areas like intense fertilizer application and farming in household-scale in densely populated areas, especially with the bad sanitation system. The distribution of nitrate contaminated groundwater was correlated to the types of land use. The monitoring of land use change is needed especially from the agricultural areas to residential areas due to excessive population growth.